2014
DOI: 10.3109/10826084.2014.949008
|View full text |Cite
|
Sign up to set email alerts
|

Tailgating and Pregaming by College Students with Alcohol Offenses: Patterns of Alcohol Use and Beliefs

Abstract: Research indicates that pregaming (drinking before a social event) and tailgating (drinking before a sporting event) are two culturally ingrained alcohol use behaviors by college students. We examined the prevalence of these two activities in a sample of college students (N = 354) who violated campus alcohol policy and were mandated to receive an alcohol intervention in fall 2010. Results indicated that alcohol consumption and other risk factors were related to pregaming and tailgating. These findings are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…We also examined whether gender predicted pregaming behaviors and found that gender was not associated with pregaming or alcohol consequences. Though some research has identified gender differences in pregaming (Barnett et al, 2013; Hustad et al, 2014; LaBrie & Pedersen, 2008; Merrill et al, 2013; Paves et al, 2012; Zamboanga et al, 2013a), the literature has been mixed, and we did not observe such differences here. Our results were consistent with some previous findings that pregaming is equally prevalent and problematic in male and female college students (DeJong et al, 2010; Haas et al, 2012; Read et al, 2010).…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…We also examined whether gender predicted pregaming behaviors and found that gender was not associated with pregaming or alcohol consequences. Though some research has identified gender differences in pregaming (Barnett et al, 2013; Hustad et al, 2014; LaBrie & Pedersen, 2008; Merrill et al, 2013; Paves et al, 2012; Zamboanga et al, 2013a), the literature has been mixed, and we did not observe such differences here. Our results were consistent with some previous findings that pregaming is equally prevalent and problematic in male and female college students (DeJong et al, 2010; Haas et al, 2012; Read et al, 2010).…”
Section: Discussioncontrasting
confidence: 63%
“…Other names for this drinking practice include pre-partying, pre-drinking, or pre-loading (Foster & Ferguson, 2014; Reed et al, 2011). Pregaming is a specific type of risky drinking that has been the focus of recent empirical attention (Ahmed, Hustad, LaSalle, & Borsari, 2014; Barnett, Orchowski, Read, & Kahler, 2013; Hustad et al, 2014; Moser, Pearson, Hustad, & Borsari, 2014; Wells, Graham, & Purcell, 2009). Pregaming is considered to be a hazardous behavior in part because heavier drinkers tend to do it (e.g., DeJong, DeRicco, & Schneider, 2010; Haas, Smith, Kagan, & Jacob, 2012) and because it is linked to higher levels of intoxication (Barry, Stellefson, Piazza-Garnder, Chaney, & Dodd, 2013; Borsari et al, 2007; Fairlie, Maggs, & Lanza, 2015) and negative consequences (Barnett et al, 2013; Kuntsche & Labhart, 2013; Labhart, Graham, Wells, & Kuntsche, 2013; LaBrie & Pedersen, 2008; Merrill, Vermont, Bachrach, & Read, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, alcohol use prior to college has emerged as the best predictor of drinking during the first year of college, which is often a period of increased alcohol use and problems (3). Three drinking practices that are associated with rapid consumption and an increased risk of experiencing negative alcohol-related problems in college students are drinking games, pregaming (drinking alcohol before attending an event) (46) and tailgating (drinking alcohol before attending and in the general vicinity of a football game) (7). As the first few weeks of college are not only critical for college success, but also for the development of drinking behaviors (8), it is vital to evaluate correlates of heavy drinking in the context of drinking games, pregaming, and tailgating.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in contrast to other high-risk drinking activities [e.g. pregaming/prepartying, or drinking before going out, Borsari et al (8); tailgating, or drinking before attending a football game, Hustad et al (9); 21st birthday celebrations, Rutledge et al (10)], some participants may not have total control over how much they drink because their consumption is determined by the rules of the game and/or other participants' behavior (e.g. targeting other gamers to drink).…”
Section: Introductionmentioning
confidence: 99%